Hipsters [videorecording (DVD)] - Todorovskiĭ, Valeriĭ, 1962-; Shagin, Anton, 1984-; Akinʹshina, Oksana; Brik, Evgenii͡a; Matveev, Maksim, 1982- (Kino Lorber, 2013)
While the Cold War heats up on the world stage, rebellious youth in 1955 Moscow wage a cultural battle against dismal Soviet conformity, donning brightly colored black-market clothing, adopting American nicknames and reveling in forbidden jazz.